Obtaining Glow Discharge Plasma Electron Density from Simple I-V Characteristics - Talal, Shamil K. (Science Journal of University of Zakho, 2013)
In this work all necessary mathematical formulation needed to calculate the approximate value of the glow discharge plasma electron density is carried out. The formulation is converted to a matlab computer code that can directly give the density. The inputs to the program are the gas pressure, breakdown potential, discharge voltage and current values, and the anode cross section area.